Peroxiredoxin 3 Inhibits Acetaminophen-Induced Liver Pyroptosis Through the Regulation of Mitochondrial ROS - Wang, Yue; Zhao, Yan; Wang, Zhecheng; Sun, Ruimin; Zou, Boyang; Li, Ruixi; Liu, Deshun; Lin, Musen; Zhou, Junjun; Ning, Shili; Tian, Xiaofeng; Yao, Jihong (Frontiers in Immunology, 2021)
Pyroptosis is a newly discovered form of cell death. Peroxiredoxin 3 (PRX3) plays a crucial role in scavenging reactive oxygen species (ROS), but its hepatoprotective capacity in acetaminophen (APAP)-induced liver disease remains unclear. The aim of this study was to assess the role of PRX3 in the regulation of pyroptosis during APAP-mediated hepatotoxicity. We demonstrated that pyroptosis occurs in APAP-induced liver injury accompanied by intense oxidative stress and inflammation, and liver specific PRX3 silencing aggravated the initiation of pyroptosis and liver injury after APAP intervention. Notably, excessive mitochondrial ROS (mtROS) was observed to trigger pyroptosis by activating the NLRP3 inflammasome, which was ameliorated by Mito-TEMPO treatment, indicating that the anti-pyroptotic role of PRX3 relies on its powerful ability to regulate mtROS. Overall, PRX3 regulates NLRP3-dependent pyroptosis in APAP-induced liver injury by targeting mitochondrial oxidative stress.